Transformasi Respons Kegawatdaruratan Berbasis Komunitas: Tinjauan Literatur Terhadap Inovasi Teknologi, Kesiapsiagaan Sosial, Dan Model Intervensi Terkini Di Era Digital - Irma Valentina Manurung; Syahferi Anwar (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This literature review aims to explore the transformation of community-based emergency response systems in the digital era, with a focus on technological innovation, social preparedness, and adaptive intervention models. Using a systematic review approach, 38 articles published between 2019 and 2024 were analyzed from databases such as Scopus, PubMed, and ScienceDirect. The findings indicate that digital applications, AI-based early warning systems, and virtual reality-based emergency training have significantly enhanced community responsiveness. Moreover, social factors such as local leadership, solidarity, and participatory simulation play a vital role in strengthening adaptive capacity. This review proposes an integrative socio-technical model that combines digital tools with community participation to improve preparedness and resilience. The implications suggest the need for inclusive and sustainable community disaster response frameworks supported by policy and cross-sectoral collaboration.